Corporate Social Responsibility Communication and Company Reputation in Pandemic Era - Adhianty Nurjanah (Komunikator, 2021)
Corporate Social Responsibility (CSR) is a way to build a company’s positive reputation. In the new media era and during the COVID-19 pandemic, online media has become an effective communication medium for companies to communicate CSR and build a positive reputation among stakeholders. This study examines BRI Peduli CSR communication during the COVID-19 pandemic through online media on the bri.co.id website that can increase BRI’s positive reputation. The research method used in this research is descriptive qualitative research with case study method, data collection is done by in-depth interview and literature study. The data analysis technique was carried out by triangulating sources to get accurate results regarding CSR communications during the COVID-19 pandemic. The results show that effective CSR communication between companies and communities that are beneficiaries of CSR programs will greatly determine the program’s success. The CSR program is an official communication channel so that all stakeholders get accountable and reliable information. BRI has also applied the principle of digitization to new media but has not yet reached the level of interactivity and audience-generated media. Online media can build a positive image and be reported CSR Program massively during the COVID-19 pandemic.